Getting a Grip on Climate Change in the Philippines : Extended Technical Report - World Bank (Washington, DC, 2014)
Philippines currently experience and will continue to face significant impacts from climate change. To ensure climate resilience, build a low-carbon economy, and increase its role in the global climate change dialogue, the Philippine government has launched strong climate policy and institutional and financing reforms, supported by a clear rationale for no-regrets action. However, transformative progress toward a more climate resilient society and low carbon economy remains limited. Carried out at mid-term of the first phase of the National Climate Change Action Plan (NCCAP), the Philippine Development Plan (2011-2016) and the current Administration, this review is an opportunity, and comes early enough, to ensure that first phase reforms are finalized and the groundwork for the second and third phases put in place. Recommendations consolidate the strategic direction of the NCCAP and set the stage for scaling up action over the next two phases. Specific activities are proposed to support eight objectives organized around three pillars: (i) strengthening the planning, execution, and financing framework for climate change; (ii) enhancing accountability through monitoring, evaluation, and review of climate change policies and activities; and (iii) building capacity and managing change.